AN ANALYSIS OF INFLUENCE OF ECONOMIC MENTALITY IS ON ECONOMIC DEVELOPMENT OF COUNTRY: CROSS-CORRELATION REGRESSIVE APPROACH - Z. Halushka; O. Luste (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article defines the role of economic mentality as an important factor of social and economic transformation, analyses methods for analyzing mental differences, carried correlation-regression analysis based on mental characteristics and indicators of social economic development, outlines the prospects for further research this issue.